Srinivasan's coagulation test in taxonomically classified streptomycetes - Ricicová, A; Pokorná, L; Sajdl, P (Folia microbiologica, 1982)
Srimivasan's coagulation test was performed in 18 strains of the genus Streptomyces and one strain of the genus Actinoplanes. The highest coagulation activity was detected in strains systematically classified in a series of streptomycetes with pink or red aerial mycelium: S. erythreus, Streptomyces sp. AJ/22, S. roseo-luteus and S. griseofuscus. With the exception of S. griscofuscus these three cultures also exhibited the highest inhibitory activity B. subtilis. When using hemoglobin as substrate it was possible to detect acid, neutral and alkaline proteinases with the highest poroteolytic activity at pH 3.0 to 4.0 in the most active strain of S. erythreus.
Keywords: antibakteriální látky; druhová specificita; bakteriologické techniky; Animals; Milk; Species Specificity; proteasy; Anti-Bacterial Agents; Actinomycetales; zvířata; Peptide Hydrolases; Streptomyces; mléko; Bacteriological Techniques